2019
DOI: 10.1017/s0022029919000025
|View full text |Cite
|
Sign up to set email alerts
|

The effects of non-esterified fatty acids and β-hydroxybutyrate on the hepatic CYP2E1 in cows with clinical ketosis

Abstract: Dairy cows with ketosis display severe oxidative stress as well as high blood concentrations of non-esterified fatty acids (NEFA) and β-hydroxybutyrate (BHB). Cytochrome P4502E1 (CYP2E1) plays an important role in the induction of oxidative stress. The aim of this study was to investigate CYP2E1 expression and activity in the liver of clinically ketotic cows (in vivo) and the effects of NEFA and BHB on CYP2E1 expression and activity in hepatocytes (in vitro). Dairy cows with clinical ketosis exhibited a low bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…To our knowledge, there are no studies that specifically investigate the relationship between CYP1A2 and ketosis in cows. However, there are studies that examine the effect of ketosis on the expression of other cytochrome P450 genes in cows, for example, Peng et al [16] found that the expression of CYP2E1 was significantly upregulated in the liver of cows with clinical ketosis compared to healthy cows. Another study by Gaddis et al [17] indicate a relationship between ketosis and CYP26B1 gene expression.…”
Section: The Mrna Expression Of Hepatocytes-specific Genesmentioning
confidence: 99%
“…To our knowledge, there are no studies that specifically investigate the relationship between CYP1A2 and ketosis in cows. However, there are studies that examine the effect of ketosis on the expression of other cytochrome P450 genes in cows, for example, Peng et al [16] found that the expression of CYP2E1 was significantly upregulated in the liver of cows with clinical ketosis compared to healthy cows. Another study by Gaddis et al [17] indicate a relationship between ketosis and CYP26B1 gene expression.…”
Section: The Mrna Expression Of Hepatocytes-specific Genesmentioning
confidence: 99%
“…2,5 Excess FFA accumulation overwhelms the hepatic processing capacity, inducing β-oxidation, which increases ketone levels and causes ketosis in dairy cows. 6,7 During ketosis, the supraphysiological circulating concentration of FFA causes mammary gland injury in dairy cows, as there is a high demand for mammary glands to produce milk. 2,8 Thus, ketosis has been associated with reduced milk yield during early lactation, causing economic losses.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ketosis is a common metabolic disease that occurs in dairy cows during early lactation and is associated with several other periparturient diseases and reduced milk yield. , Ketosis susceptibility has been associated with an imbalance between the increased nutrient demands of lactation and a decrease in dry matter intake (DMI) during the postpartum transition period, , which elevates fat mobilization and increases fatty acid (FFA) concentration in the blood. , Excess FFA accumulation overwhelms the hepatic processing capacity, inducing β-oxidation, which increases ketone levels and causes ketosis in dairy cows. , During ketosis, the supraphysiological circulating concentration of FFA causes mammary gland injury in dairy cows, as there is a high demand for mammary glands to produce milk. , Thus, ketosis has been associated with reduced milk yield during early lactation, causing economic losses …”
Section: Introductionmentioning
confidence: 99%
“…The NEB initiates fat mobilization followed by a significant increase in blood concentrations of free fatty acids (FFA), which are the hallmark of NEB status (Duffield et al, 1998;Itle et al, 2015). Because an overload of hepatocytes with FFA is beyond the processing capacity of the liver, a large number of ketones is synthesized, among which the dominant is BHB, leading to the onset of ketosis (Peng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%